(untitled) (American Journal of Islam and Society, 2009)
The Centre for Poverty and Development Studies (CPDS), Faculty of Economics and Administration, University of Malaya, hosted an international conference, “Managing Sustainable Development and PovertyAlleviation in the IslamicWorld,” on 14-15 October 2008 in Kuala Lumpur, Malaysia. This event attracted around 100 participants and eighteen presenters. The thematic foci reflected the understanding that the Islamic world exhibits significant and disturbing variations in its levels and magnitudes of socioeconomic development, poverty incidence and prevalence, income distribution patterns, literacy, employment, and economic growth.As these are inconsistent with Islam’s principles and ethics of distributive justice and equity, unity, and social responsibility, Muslim researchers and concerned individuals must join the quest to devise concerted and collaborative Islamic solutions to the challenges of sustainable development, as well as of poverty alleviation and eradication, in the Islamic world. Within an Islamic framework, the presenters analyzed poverty as a socioeconomic phenomenon from multiple perspectives. One perspective justifies the instrumentality of empowerment in overcoming poverty in Islamic societies. As the poor are powerless, the universal principles of equality and justice imply a more equitable power distribution in society, and collective social action implies consultation strategies to resolve social imperfections. InMalaysia’s three poverty-focused organizations, empowerment was analyzed using a framework of determinants, including trusting the organizer, local working culture, participants behaving like friends, the government’s role, importance of the organization, belief in and trusting the organization, and roles at all levels. It was established that individuals, the community, and the organization widely acknowledge empowerment as a significant determinant for success ...